The Influence of Organizational Culture on Employees’ Commitment: An Empirical Study In 22 Joint-Stock Commercial Banks in Viet Nam - Hue HOANG THI; Hoc LE HIEU; Mai Anh NGUYEN THI (Communications of International Proceedings, 2022)
This paper is aiming to examine the influence of organizational culture on employee’s commitment in the context of Vietnam’s banking industry. Based on a survey from emplyees of 22 joint-stock commerceial banks in Vietnam, the research confirmed that five factors of organizational culture (including teamwork, communication, training and development, reward and recognition, and leadership style) have significant correlation with employee’s commitment.
Keywords: Organizational culture; employee’s commitment; leadership style; joint-stock commercial bank; Viet Nam